Health-technology in the classroom with the girls playing football of secondary school age - Tkachenko, S.N. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Purpose : carry out a theoretical analysis of the problem of health-use technology on football lessons in secondary schools. Material: processed more than 100 literary sources. Results : the article presents the main ways of implementation of maintaining health technology on football lessons. The basic attention approaches to the concept of «maintaining health». An author analyses the classifications of maintaining health technology and basic principles of their application of the lessons of football in secondary schools. The author summarized the current views on the problem of implementation the maintaining health technology in the school system, including such as monitoring the causes of injuries on football lessons and ways to prevent them, the creation of healthy environments. Conclusion : It is proved that the use of maintaining health technology on football lessons aims not only development of pupil’s skills, healthy lifestyles, but also the creation of educational institution necessary conditions for preserving the health of the younger generation.